Crises, capital controls, and financial integration - Eduardo Levy Yeyati; Sergio L. Schmukler; Neeltje van Horen (Asian Development Bank Institute (ADBI), 2008)
This paper analyzes the effects of capital controls and crises on financial integration, using stocks from emerging economies that trade in both domestic and international markets. The cross-market premium (the ratio between the domestic and the international market price of cross-listed stocks) provides a valuable measure of how capital controls and crises affect international financial integration. The paper shows that, contrary to the common perception that capital controls can be easily evaded, they do affect the cross-market premium in a sustainable way. Controls on capital inflows put downward pressure on domestic markets relative to international ones, generating a negative premium. The opposite happens with controls on capital outflows. This signals the inability of market participants to engage in perfect arbitrage, due to the segmentation of domestic markets from international ones. Crises affect financial integration by generating more volatility in the premium and putting more downward pressure on domestic prices.
Keywords: F30; F36; G15; 330